HELEN’S STRUGGLE FOR CARING CHILDREN REFLECTED IN GARRY MARSHALL’S RAISING HELEN (2004): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - ERNAWATI, ERNAWATI (2011)
This research paper elaborates the struggle for caring children in Garry Marshall’s Raising Helen movie that is analyzed through in individual psychological approach. The objectives of the research are to analyze the structural elements of the movie and to analyze the movie based on individual psychological approach. This research belongs to a descriptive qualitative research. The data of the research is the movie entitled Raising Helen whereas the data source comes from both primary data source which is in the form of the script of the movie being researched and secondary data source related to the research as some books of individual psychological theories, internet and other relevant information. Based on the analysis, the researcher comes to the following conclusions: Garry Marshall presents the main character of Helen that is drawn as a young woman who has carefree life style that suddenly has to responsible for caring three children after the death of her sister. During the flow of the story Helen experiences obstacle that take maturation for her.